Structures Congress 2014 2014
DOI: 10.1061/9780784413357.030
|View full text |Cite
|
Sign up to set email alerts
|

Damage Detection on Structures Using Texture Mapped Laser Point Clouds

Abstract: Damage due to age or accumulated damage from hazards on existing structures poses a worldwide problem. In order to evaluate the current status of aging, deteriorating and damaged structures, it is vital to accurately assess the present conditions. It is possible to capture the in situ condition of structures by using laser scanners that create dense 3D point clouds. However, extracting meaningful information from point clouds automatically is challenging, and the current state-of-the-art requires a certain amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Armesto-González et al [ 41 ] employed LIDAR intensity data to detect degraded stony materials in scans of historic buildings. Several researchers used LIDAR intensity to detect cracks in concrete structural components in their laboratory tests or post-disaster field investigations [ 42 , 43 , 44 ]. Kashani et al [ 46 , 47 , 48 ] indicated that the LIDAR intensity data is an appropriate means to automatically detect cladding damage of buildings after wind storm events.…”
Section: Applications Of Lidar Intensitymentioning
confidence: 99%
“…Armesto-González et al [ 41 ] employed LIDAR intensity data to detect degraded stony materials in scans of historic buildings. Several researchers used LIDAR intensity to detect cracks in concrete structural components in their laboratory tests or post-disaster field investigations [ 42 , 43 , 44 ]. Kashani et al [ 46 , 47 , 48 ] indicated that the LIDAR intensity data is an appropriate means to automatically detect cladding damage of buildings after wind storm events.…”
Section: Applications Of Lidar Intensitymentioning
confidence: 99%
“…However, only a few studies have been found to specifically identify the structural deformation and materials behavior of the building based on attribute point cloud information. For example, Armesto-González et al [38], Guldur and Hajjar [39], and Olsen et al [40] similarly examined surface degradation of buildings, mainly based on the intensity information. Several works have also been identified to utilize RGB color information for crack detection of the building surface.…”
Section: Related Workmentioning
confidence: 99%
“…However, existing damage complicated the classification procedure which was dependent on identifying geometric features such as the corner edge of a beam. To detect damage within structural members from point clouds, Guldur and Hajjar 22 employed the calculation of vertex normals and compared it to a reference vector. The reference vector was constructed based on the analyzing member direction, which demanded a preprocessing step to identify the skeleton geometry.…”
Section: Introductionmentioning
confidence: 99%